2010 Fourth International Conference on Network and System Security 2010
DOI: 10.1109/nss.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Ignorant Experts: Computer and Network Security Support from Internet Service Providers

Abstract: -The paper examines the advice and support provided by seven major Internet Service Providers in Australia through late 2009 and early 2010 in relation to computer and network security. Previous research has indicated that many end-users will attempt to utilise the support provided by Internet Service Providers as a simple and effective method by which to obtain key information in regards to computer security. This paper demonstrates that in many cases the individuals working at the help desk are either reluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, in 2010 it was identified that many ISP's do not employ staff with an adequate understanding and expertise in countering Internet based threats. Instead staff tend direct end-users to information found on the ISP website [6]. Unfortunately ISP websites provide very few solutions to protect end-users [7].…”
Section: Introduction (Heading 1)mentioning
confidence: 99%
“…However, in 2010 it was identified that many ISP's do not employ staff with an adequate understanding and expertise in countering Internet based threats. Instead staff tend direct end-users to information found on the ISP website [6]. Unfortunately ISP websites provide very few solutions to protect end-users [7].…”
Section: Introduction (Heading 1)mentioning
confidence: 99%